1990
DOI: 10.1111/j.1365-2796.1990.tb00245.x
|View full text |Cite
|
Sign up to set email alerts
|

Trimethoprim‐sulphamethoxazole‐associated blood dyscrasias. Ten years'experience of the Swedish spontaneous reporting system

Abstract: During the 10-year period 1976-1985, a total of 154 cases of blood dyscrasia were reported in Sweden which were evaluated as having a probable or possible causal relationship with trimethoprim-sulphamethoxazole (T-SM). There were 61 cases of leucopenia (of which 16 had agranulocytosis), 28 cases of thrombocytopenia, and two of non-haemolytic anaemia. There were also 32 cases of bicytopenia and 31 cases of tricytopenia. The median age varied from 38 years in the leucopenia group to 81 years in those with tricyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(46 citation statements)
references
References 9 publications
0
45
1
Order By: Relevance
“…Although SMX-TMP administration may cause drug-induced aplastic anemia, several studies (30,31) failed to find this association. Keisu et al (31) found that SMX-TMP induced anemia, but that this effect was sporadic.…”
Section: Discussionmentioning
confidence: 99%
“…Although SMX-TMP administration may cause drug-induced aplastic anemia, several studies (30,31) failed to find this association. Keisu et al (31) found that SMX-TMP induced anemia, but that this effect was sporadic.…”
Section: Discussionmentioning
confidence: 99%
“…, tacrolimus (5), sirolimus (6), cotrimoxazole (7), omeprazole (8), rituximab (9) and angiotensin converting enzyme inhibitors (10). Drug imputability often remains difficult to establish directly, and regression of neutropenia after drug discontinuation can be used as indirect evidence.…”
Section: Several Drugs Used In Kidney Transplantation Can Induce Signmentioning
confidence: 99%
“…The incidence of severe hematologic toxicity is unknown, but estimates range up to 1.7-5.5/100 000 prescriptions. 9,10 Several mechanisms have been implicated and described in case reports ( Table 2). Generation of antibodies to the glycoprotein IIb/IIIa complex on platelets can cause immune thrombocytopenia, which is typically observed within the first week of treatment and is generally reversible on discontinuation of the drug.…”
Section: O: Decreased Oxygen-carrying Capacity and Other Hematologic mentioning
confidence: 99%